Just outside this skin - D. Celermajer (Law Text Culture, 1998)
Imagine that white Australia is reclining (nervously) on Freud's couch. Twitches a little and adjusts himself (with discomfort) against the Persian covered cushions. What would the master of psychoanalysis make of his speech? The conceit is, of course, absurd. The couch would quickly splinter beneath the weight of the bodies which make up the fiction of 'white Australia'. And Sigmund (even in his younger years) wouldn't be able to decipher a single phrase for the confusion of voices. But indulge nevertheless. Take the voice that comes straight from mid-morning radio talk back; or the 'battler' who lives in politicians' speech notes.